2009
DOI: 10.1007/s00436-009-1434-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of avian malaria parasite in mosquitoes collected at a zoological garden in Japan

Abstract: Several species of captive birds at zoological gardens of Japan were found to be infected with avian Plasmodium. However, incriminated vector mosquito species have not been identified yet. To indicate the competent vectors of avian malaria parasite, we collected mosquitoes at a zoological garden in Japan and examined for the avian malaria parasite DNA. Totally, 1,361 mosquitoes of 11 species were collected in the zoological garden of Kanagawa, the south of Tokyo in Japan in 2005. Captured mosquitoes were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 25 publications
6
33
0
Order By: Relevance
“…The interactions between malaria parasites and their vectors are complex and can be affected by both genetic and environmental factors (Tripet et al 2008). Recently, several studies have used molecular markers to examine the distribution of avian malaria parasite lineages in wild-caught vectors (Gager et al 2008, Istiaq et al 2008, Ejiri et al 2009, Kim et al 2009, Kim & Tsuda 2010, Kimura et al 2010. However, the "parasitevector-vertebrate host" interactions remain understudied for avian malaria, particularly in tropical countries.…”
mentioning
confidence: 99%
“…The interactions between malaria parasites and their vectors are complex and can be affected by both genetic and environmental factors (Tripet et al 2008). Recently, several studies have used molecular markers to examine the distribution of avian malaria parasite lineages in wild-caught vectors (Gager et al 2008, Istiaq et al 2008, Ejiri et al 2009, Kim et al 2009, Kim & Tsuda 2010, Kimura et al 2010. However, the "parasitevector-vertebrate host" interactions remain understudied for avian malaria, particularly in tropical countries.…”
mentioning
confidence: 99%
“…, Yukita SATO 1) *, Kyeong-Soon KIM 2) , Mikako TAMASHIRO 3) , Yoshio TSUDA 2) , Takako TOMA 3) , Ichiro MIYAGI 3) , Koichi MURATA 4) and Masayoshi YUKAWA 4) Avian Plasmodium spp. are blood protozoa that cause the vector-borne disease of bird malaria on a worldwide scale and are transmitted mainly by mosquitoes of the genera Aedes, Anopheles, Culex and Culiseta [20].…”
mentioning
confidence: 99%
“…are blood protozoa that cause the vector-borne disease of bird malaria on a worldwide scale and are transmitted mainly by mosquitoes of the genera Aedes, Anopheles, Culex and Culiseta [20]. Previous studies in Japan reported that several species of wild and captive birds were infected with various strains of avian Plasmodium [10][11][12], and some mosquito species were reported as their vectors [2][3][4][5][6][7]. Elucidating the prevalence and transmission pathways of avian Plasmodium may provide important information for evaluating the risk of parasite infections in the study areas [3,4].…”
mentioning
confidence: 99%
See 2 more Smart Citations